A comprehensive study on lithium-based reactive hydride composite (Li-RHC) as a reversible solid-state hydrogen storage system toward potential mobile applications. Issue 37 (30th June 2021) - Karimi, Fahim; Pranzas, Philipp Klaus; Puszkiel, Julián Atillio; Castro Riglos, María Victoria; Milanese, Chiara; Vainio, Ulla; Pistidda, Claudio; Gizer, Gökhan; Klassen, Thomas; Schreyer, Andreas; Dornheim, Martin
Abstract : Superb dehydrogenation/hydrogenation kinetic enhancement of the LiBH4 –MgH2 reactive hydride composite system by addition of NbB2 nano-particles as nucleation agents for MgB2 . Abstract : Reversible solid-state hydrogen storage is one of the key technologies toward pollutant-free and sustainable energy conversion. The composite system LiBH4 –MgH2 can reversibly store hydrogen with a gravimetric capacity of 13 wt%. However, its dehydrogenation/hydrogenation kinetics is extremely sluggish (∼40 h) which hinders its usage for commercial applications. In this work, the kinetics of this composite system is significantly enhanced (∼96%) by adding a small amount of NbF5 . The catalytic effect of NbF5 on the dehydrogenation/hydrogenation process of LiBH4 –MgH2 is systematically investigated using a broad range of experimental techniques such as in situ synchrotron radiation X-ray powder diffraction ( in situ SR-XPD), X-ray absorption spectroscopy (XAS), anomalous small angle X-ray scattering (ASAXS), and ultra/small-angle neutron scattering (USANS/SANS). The obtained results are utilized to develop a model that explains the catalytic function of NbF5 in hydrogen release and uptake in the LiBH4 –MgH2 composite system.